2021
DOI: 10.24036/0202152109548-0-00
|View full text |Cite
|
Sign up to set email alerts
|

In vitro analysis: inhibitory effect of Phyllanthus niruri extract against Aeromonas salmonicida

Abstract: The purpose of this research is to explore effectiveness from every part of Phyllanthus niruri such as leaves (L), fruits (F), stem (S) and combination (C) of those parts that able to inhibit Aeromonas salmonicida growth by using different methods of extraction both infundation and maceration. Experiments has been done at Budidaya Perairan Laboratory, Sriwijaya University. In vitro analysis used tetracycline 30 µg/ml as positive control, bacterial culture at 10 14 CFU/ml and concentration of each part of stone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…The Meniran leaf ethanolic extract contained: saponins, tannins, flavonoids, polyphenols, and alkaloids (Table 5). This was in accordance with several previous studies that meniran leaves contained saponins, tannins, flavonoids [12], alkaloids [10,16], polyphenols [14]. A previous study has shown that Kenikir leaves contained saponins, tannins, alkaloids, flavonoids, and polyphenols [20,[35][36][37], following the present study (Table 5).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The Meniran leaf ethanolic extract contained: saponins, tannins, flavonoids, polyphenols, and alkaloids (Table 5). This was in accordance with several previous studies that meniran leaves contained saponins, tannins, flavonoids [12], alkaloids [10,16], polyphenols [14]. A previous study has shown that Kenikir leaves contained saponins, tannins, alkaloids, flavonoids, and polyphenols [20,[35][36][37], following the present study (Table 5).…”
Section: Discussionsupporting
confidence: 93%
“…The condenser was mounted on a rounded bottom flask, containing the solution. This method was carried out three times in circulation, with no water dripping on the scale tube, occurred for 15 min [12].…”
Section: Moisture Content Determination Of Meniran and Kenikir Leaf P...mentioning
confidence: 99%
See 1 more Smart Citation